2008
DOI: 10.1007/s12072-008-9103-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of hepatitis B virus infection: analysis of mass screening in Hawaii

Abstract: Background Although hepatitis B seroprevalence has been studied extensively in California and New York, detailed information for other high-risk areas in the United States is lacking. To study current prevalence and risk for hepatitis B virus (HBV) infection in Hawaii, we analyzed cross-sectional data from Hawaii residents screened between July 2003 and April 2006. Methods We retrospectively reviewed the screening records of 3,989 participants recruited at health fairs and clinics. Prevalence and risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
2
9
1
Order By: Relevance
“…On the other hand, living in a rural area was not found as a risk factor for transmission of hepatitis B. Some studies have reported that there was a significant seropositivity difference between rural and urban regions 20, 26. There are 56 ethnic groups in China and the lifestyle of the minority ethnic population is considerably different from the Han majority ethnic population.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, living in a rural area was not found as a risk factor for transmission of hepatitis B. Some studies have reported that there was a significant seropositivity difference between rural and urban regions 20, 26. There are 56 ethnic groups in China and the lifestyle of the minority ethnic population is considerably different from the Han majority ethnic population.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is likely that the findings are related to differences in lifestyle or behaviors among males and females, such as smoking, drinking, extensive social range, physical activity, dining out, hygiene, and sexual activity. Luo et al and Tsai et al reported that inhabitants of the plain regions had lower rates of infection than those living in island regions (7, 19). However, differences in HBeAg positivity among regions have remained unknown.…”
Section: Discussionmentioning
confidence: 98%
“…A convenience sample of patients screened for hepatitis B at health fairs and clinic settings in Hawaii found that 10.7% of Pacific Islanders were seropositive for Hepatitis B (Tsai, Holck, Wong, and Ricalde, 2008).…”
Section: Hepatitis Bmentioning
confidence: 99%